The Long and Short of Next Generation Sequencing for Cryptosporidium Research - Mkandawire, Tapoka T.; Sateriale, Adam (Frontiers in Cellular and Infection Microbiology, 2022)
The intestinal parasite Cryptosporidium is a significant cause of severe diarrhoeal disease that can have long term effects. Therapeutic options remain limited despite a significant impact on public health, partly due to various challenges in the field of Cryptosporidium research, including the availability of genomic and transcriptomic data. In this review we explore how long read DNA and RNA sequencing technologies have begun to provide novel insights into the biology of the parasite. The increased deployment of these technologies will help researchers address key gaps in the understanding of Cryptosporidium biology, and ultimately drive translational research and better parasite control.